2012
DOI: 10.1242/jeb.063677
|View full text |Cite
|
Sign up to set email alerts
|

Wired to run: exercise-induced endocannabinoid signaling in humans and cursorial mammals with implications for the ‘runner’s high’

Abstract: SUMMARYHumans report a wide range of neurobiological rewards following moderate and intense aerobic activity, popularly referred to as the ʻrunnerʼs highʼ, which may function to encourage habitual aerobic exercise. Endocannabinoids (eCBs) are endogenous neurotransmitters that appear to play a major role in generating these rewards by activating cannabinoid receptors in brain reward regions during and after exercise. Other species also regularly engage in endurance exercise (cursorial mammals), and as humans sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
154
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(163 citation statements)
references
References 53 publications
(106 reference statements)
8
154
0
1
Order By: Relevance
“…With the emergence of Homo erectus ∼1.8 million y ago, paleontological and archaeological evidence indicate a major shift in hominin evolution characterized by increases in brain and body size (53), improved locomotor efficiency (54), larger home ranges, and increased mobility (55). This long evolutionary history of high levels of terrestrial mobility in the genus Homo, together with the evidence of selection for endurance running (56,57), strongly suggests that the human locomotor skeleton evolved in a mechanical and physiological context that involved persistent and frequent loading throughout life. This study provides support for the assertion that contemporary humans live in a cultural and technological milieu incompatible with our evolutionary adaptations (58), and highlights the importance of physical activity and exercise for bone health and the attenuation of age-related bone loss, osteoporosis, and fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…With the emergence of Homo erectus ∼1.8 million y ago, paleontological and archaeological evidence indicate a major shift in hominin evolution characterized by increases in brain and body size (53), improved locomotor efficiency (54), larger home ranges, and increased mobility (55). This long evolutionary history of high levels of terrestrial mobility in the genus Homo, together with the evidence of selection for endurance running (56,57), strongly suggests that the human locomotor skeleton evolved in a mechanical and physiological context that involved persistent and frequent loading throughout life. This study provides support for the assertion that contemporary humans live in a cultural and technological milieu incompatible with our evolutionary adaptations (58), and highlights the importance of physical activity and exercise for bone health and the attenuation of age-related bone loss, osteoporosis, and fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…CB-2 receptors are found in the periphery, including lymph tissue, and in lower concentrations in some brain regions, including the periaqueductal gray. Activation through G-coupled membrane proteins causes physiologic responses expected from these regions, including feelings of well-being or psychosis (depending on the "dose" of THC), impaired memory and cognitive processing, slowed locomotor function, as well as antinociceptive, 3 antiemetic, antispasticity, and sleep-promoting effects. Receptor activation inhibits adenylate cyclase, converting cyclic adenosine monophosphate to adenosine triphosphate, and inhibits release of multiple neurotransmitters, including acetylcholine, dopamine, and glutamate, when neuronal excitation is present.…”
mentioning
confidence: 99%
“…The major short term effect of exercise is euphoria, which is colloquially known as "runner's high" in distance running or "rower's high" in crew (Raichlen et al, 2012). Recent researches and medical reviews have shown that endogenous euphoriants such as betaphenylamide (stimulant), beta-endorphin (an opiod), and anandamide are responsible for producing exercise related euphoria.…”
Section: Neurobiological Effectsmentioning
confidence: 99%